Pengaruh Analisis Kebangkrutan Model Altman Z-score Terhadap Harga Saham Pada Perusahaan Manufaktur di Bursa Efek Indonesia Sebelum dan Saat Pandemi Covid -19 (Studi Kasus Tahun 2019-2020) - Ayyu Dila Anggraeny; Ade Suryana (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
This study aims to determine the effect of the Altman Z-Score on stock prices, the effect of the ratios on the Altman Z-score on stock prices before and during the covid-19 pandemic, and to find out the differences in the ratios of the Altman Zscore before and during the pandemic. covid-19 in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period. This type of research uses a quantitative approach with purposive sampling method. There are 14 sample companies that match the specified criteria. The results of this study indicate that in simple linear regression the Altman Z-score value has no effect on stock prices before the covid-19 pandemic and during the covid-19 pandemic.